Digital cash transfers from the perspective of intended beneficiaries: A comparative exploration of effectiveness - Heba Al Fara (University of Bath, Centre for Development Studies (CDS), 2023)
Digitalization has been identified as a primary aim for humanitarian organizations because it is rapidly altering the way humanitarian logistics and aid activities are implemented, directly affecting the way the humanitarian field supports those in need. Nonetheless, digital humanitarian tools are usually designed to meet the requirements of humanitarian aid agencies, not aid recipients, using top-down innovations, which creates a gap in aid beneficiary perspectives and experiences to enhance the utility of digital aid mechanisms. Using two NGO's reports of beneficiary experiences, this paper compares the experiences of aid beneficiaries in the Democratic Republic of the Congo and Kenya using mobile money, and illustrates different effectiveness outcomes from the perspective of aid recipients.. This paper shows that the context in which mobile money is implemented according to four main factors identified in the literature - access to target populations, sustainability of programming, data protection, and ethical concerns in delivery - determines aid recipient experiences and views of mobile money effectiveness.
Keywords: 330; mobile money; intended beneficiary experience; effectiveness; comparative study